2015
DOI: 10.1186/s12936-015-0909-7
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of intermittent preventive treatment for malaria in pregnancy and intense drug resistance in western Uganda

Abstract: BackgroundIntermittent preventive treatment in pregnancy (IPTp) with sulfadoxine–pyrimethamine (SP) is widely implemented in sub-Saharan Africa for the prevention of malaria in pregnancy and adverse birth outcomes. However, in areas of intense SP resistance, the efficacy of IPTp may be compromised.MethodsA cross-sectional study among 915 delivering women (728 analysable live singleton deliveries) was conducted in Fort Portal, western Uganda, to assess associations of reported IPTp use, Plasmodium falciparum in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
65
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 41 publications
8
65
2
Order By: Relevance
“…Sulfadoxine/pyrimethamine (SP) is recommended by the WHO as intermittent preventative treatment (IPTp) for the prevention of malaria in pregnancy in sub‐Saharan Africa 6. IPTp with SP is administered in at least two doses, starting in the second trimester of pregnancy after quickening, with an interval of at least 4 weeks 4.…”
mentioning
confidence: 99%
“…Sulfadoxine/pyrimethamine (SP) is recommended by the WHO as intermittent preventative treatment (IPTp) for the prevention of malaria in pregnancy in sub‐Saharan Africa 6. IPTp with SP is administered in at least two doses, starting in the second trimester of pregnancy after quickening, with an interval of at least 4 weeks 4.…”
mentioning
confidence: 99%
“…The triple Pfdhfr mutation N51I, C59R, and S108N in combination with the double A437G and K540E Pfdhps mutant formed a quintuple mutant haplotype, which confers a high risk of treatment failure with SP 6. Recent studies have shown an increase in Pfdhps mutations at A581G, thus further escalating the risk for even higher levels of resistance and significant decreases in the effectiveness of SP as IPTp 7,8…”
Section: Introductionmentioning
confidence: 99%
“…This scenario contrasts with a previous study in which up to 25% of pregnant women reporting nonuse of SP were found to have residual drug when tested [34]. Many previous studies reporting ineffectiveness of SP-IPTp have relied on self-reports and ANC records as proof of SP use [14, 15, 19]. Where no effort is made to ascertain actual user compliance, such findings remain questionable, especially coming from resource-constrained settings where unsupervised administration of SP is the norm, contrary to guidelines.…”
Section: Discussionmentioning
confidence: 75%
“…These concerns have been largely driven by the rising prevalence of higher-level SP resistance mutations. To this end, recent studies from areas with high prevalence of resistance mutations have reported reduced efficacy of SP-IPTp [14, 15, 19, 20]. However, such findings in most cases are hampered by the exclusive reliance on self-reports and antenatal records to ascertain SP use.…”
Section: Introductionmentioning
confidence: 99%